Web Center Design of Student Activity Unit (UKM) Universitas Muhammadiyah Sidoarjo as a Center for Membership Information Event and Product Marketing: Perancangan Web Center Unit Kegiatan Mahasiswa (UKM) Universitas Muhammadiyah Sidoarjo Sebagai Pusat Informasi Keanggotan, Event dan Pemasaran Produk - Zahputra, Aldy Trisza; Eviyanti, Ade; Rosid, Mochamad Alfan; Hindarto, Hindarto (Universitas Muhammadiyah Sidoarjo, 2023)
Information systems and technology are advancing so rapidly that technology and people no longer play separate roles. One of the technologies currently being developed is a website-based information system. The website is a collection of linked pages and related files. Websites have been widely used by non-profit and non-profit organizations to provide accurate information to the public by functioning as a platform for information dissemination. The purpose of this research is to create a central web information system to display complete detailed data regarding the Sidoarjo Muhammadiyah University Student Activity Unit online. The research method used is the waterfall method using blackbox testing. From the test results the researchers succeeded in implementing a student activity unit website that displayed information in the form of info on achievements, works, events, products, articles, announcements and members from each UKM. With this system, student activity units can record every activity, reduce the risk of loss or damage to data and make it easier to record all of its members.